VALUES OF DA’WAH IN BANJAR PAMALI - Nasruddin, Nasruddin; Rifa’i, Akhmad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 19 No 1 (2023), 2023)
Banjar Pamali is still used in the life of the Urang Banjar community. However, on the other hand, Banjar pamali are often associated with superstitions and only believe in the supernatural.  So that many consider that Banjar pamali is an act of polytheism. This study aims to explain that not all Banjar pamali lead to acts of polytheism and superstition, but there are several verses in Banjar pamali that also contain da'wah values. The data used by the authors in this study are data obtained from literature studies.  The collected data will be analyzed semiotically with interpretive techniques.  This research is a type of literature review research by looking for theoretical references that are relevant to the cases or problems found. The results of this study prove that there are some da'wah values ​​contained in the Banjar pamali oral tradition, namely sharia values ​​and morals. With that it can be said that Banjar pamali are not all related to superstition or polytheism.  because of that there are many more oral literary traditions that are considered tabu and even shirk apart from Banjar pamali even though there are da'wah values ​​in them.